Personality and user experience (UX) in social networks - Osuagwu, Amanda Ozichi (2013)
Human personality has been linked to user behaviour in social networking sites (SNS) in several studies. However, most of these studies focus on the link between an individual's personality and how they use the SNS. This study on the other hand, focuses on the relationship between personality and an individual's user experience (UX) in the use of the SNS. The research strategy implemented included conducting two separate studies, a diary/interview study and a survey. The study revolved around the use of Facebook, which is currently one of the most widely used social networking sites. Both studies measured UX engendered from the use of Facebook and also calculated participants' personality, based on the Five Factor Model (FFM) framework and focusing on the specific traits, Extraversion and Openness to experience. These two traits were selected because they have been linked in existing research to the use of social media. There were eight participants in the diary study and 49 for the survey. Both studies involved the completion of a personality questionnaire which calculated participants' extraversion and openness to experience scores. In the diary study, participants kept a diary for a period of five days. The diary entries made were used to measure UX while in the survey a UX evaluation tool, AttrakDiff questionnaire, was used. The existence of a relationship between the personality measures and UX scores was then investigated using Pearson's correlation and a two-way ANOVA. Despite the expectation that people who scored highly on the extraversion and openness scale would have higher UX scores, the results of the analysis showed no correlation between UX scores and those personality traits. This study highlights the complexity involved in the study of UX. While most participants gave high scores for efficiency in their Facebook diary sessions, they stated during the interviews that neither the efficiency of the application or the task completion time really affected how they felt about the session. Their feelings were tied more to their expectations for that session and to what exactly happened during the session. This dissertation recommends further research to fully understand the factors that affect UX in the use of social networking sites.